A Review on Entrepreneurship Management Training on Rural Development & Women Empowerment: Unleashing Rural Potential: The Impact of Entrepreneurship Management Training on Women Empowerment (Journal of Advances and Scholarly Researches in Allied Education, 2020)
entrepreneurship management training programs have emerged as a powerful tool forpromoting rural development and empowering women in various societies worldwide. These programsaim to equip individuals, particularly those in rural areas, with the necessary skills, knowledge, andresources to start and manage successful businesses. By focusing on rural development and women'sempowerment, entrepreneurship management training addresses two critical aspects of socioeconomicprogress. Additionally, women in rural areas often encounter additional barriers, includingcultural norms, limited educational opportunities, and restricted access to financial resources anddecision-making power. Consequently, women's potential contributions to economic growth andcommunity development remain largely untapped. This paper ain to review on entrepreneurshipmanagement training on rural development women empowerment